Enhanced Heat Transfer Performance of Vapor Compression Refrigeration Systems Using Silver Nanoparticles - Fakhre Alam Khan; Hamad Aftab; Ahmed Khan; Haris A. B. Ashraf; Muhammad Bilal Ghouri; Zahid Ullah (Journal of Nanotechnology)
This novel work shows the experimental analysis of the use of silver nanoparticles (AgNPs) and their effect on the vapor compression refrigeration system (VCRS) performance. AgNPs were synthesized and confirmed through X-ray diffraction (XRD) and scanning electron microscopy (SEM) and then introduced to the VCRS. The SEM images of the AgNPs show that the size of synthesized AgNPs was between 200 nm and 500 nm. AgNPs were mixed with the polyalkylene glycol (PAG) oil in 0.017 V/V concentration, which was then used in the compressor. The comparison of the performance parameters of VCRS shows that with the inclusion of AgNPs, the work done by the compressor is reduced by 11.48%. Heat addition by the evaporator (refrigeration effect) is increased by ∼ 0.40%, which results in an overall improvement of 13% in the coefficient of performance (COP) of VCRS. Using the numerical equations available in the literature, the effective thermophysical properties were also calculated for the different concentrations of AgNPs. The calculated values confirmed that the effective thermal conductivity increases with an increase in the concentration of AgNPs in the refrigerant. This confirmed that including AgNPs in the system improved the heat transfer properties, thus improving the VCRS performance.